Optimalisasi Kader PKK Kelurahan Ciroyom Melalui Program Edukasi serta Skrining Pap Smear dan Tes IVA sebagai Preventif Kanker Serviks: Optimizing the PKK Cadres in Ciroyom Village Through Educational Programs and Pap Smear Screening and IV Tests as Cervical Cancer Prevention - Meike Rachmawati; Mira Dyani Dewi; Muhammad Syah Misuari Sabirin; Rizky Suganda Prawiradilaga; Nabilah Yahdiani Darmawan; Faradilla Azzahra Dinariansyah; Reyiena Kusumaryani Rahmat; Aninditya Putri Anugrah; Nazmy Noor Laila; Afni Nur Hasanah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Cervical cancer remains one of the leading causes of morbidity and mortality among women worldwide, particularly in developing countries such as Indonesia. Low awareness and participation in early detection programs such as Visual Inspection with Acetic Acid (VIA) and Pap smear contribute to the high incidence of advanced-stage cervical cancer. The Family Welfare Empowerment (PKK) cadres play a crucial role as community health agents in promoting cervical cancer prevention and early detection. This community service activity aimed to strengthen the capacity of PKK cadres in Ciroyom Village to educate women on early detection of cervical cancer through health education and screening using VIA and Pap smear tests. The program consisted of three stages: coordination with the Women’s Health Division (Pokja IV), an interactive educational session delivered by an obstetrics and gynecology specialist accompanied by pre- and post-tests, and voluntary VIA and Pap smear examinations conducted by medical professionals. A total of 35 cadres participated, and 18 (51.4%) underwent screening. The mean knowledge score increased significantly from 82.92% (pre-test) to 88% (post-test) (p<0.05). All participants had negative VIA results (100%), while Pap smear results showed 17 participants (94.4%) were negative for intraepithelial lesions or malignancy (NILM), and one participant (5.6%) showed ASCUS (Atypical Squamous Cells of Undetermined Significance). The results indicate that health education effectively improved cadres’ knowledge and awareness.